Sustainable Development: Anthropocentric Conditionalities and South American Biocentric Alternatives - Gudynas, Eduardo (2024)
In this article, different ideas of sustainable development are reviewed showing that they rest on ways of recognizing and assigning values. Despite its importance, this feature has not received the attention it deserves. The dominant valuation perspective is anthropocentric, which turns to behave as a conditionality that subordinates ecological imperatives and is functional to economic growth. Radical different perspectives are South American Andean-Amazonian alternatives based on a biocentric posture that recognizes intrinsic values in nature. Ecuador offers a case study of that perspective. It is argued that it represents a more powerful option because is an alternative beyond any variety of development.